Hormonal treatment and rooted cutting technique for vegetative propagation of Sungkai (Perenomo canescens Jack) - Muhammad A'kif Abdul Rahman (2018)
Stem cuttings methodology and hormones treatment were well known as method that can increase the rate of growth for plantation in circumstance of speciﬁc ambient environment. Objectives of this study are to determine root formations and growth of Sungkai stem cutting treated with different concentration of hormones lndole-3-Butanie Acids (IBA). Different cOl’1C6l’1iI‘ﬂIlOTlS of IBA hormones are expected to have different response of growth towards morphological development of Sungkai cuttings. Reaction from 3 different parts of cutting P.canescens (upper, middle and lower) was determines based speciﬁed concentrations of IBA hormones (500 ppm, 750ppm and lO00ppm). Furthermore, this experiment also proposed to determines the most effective cutting parts of Sungkai tree towards cutting techniques and hormonal treatment. Overall, this study showed positive interaction between root growth of Sungkai cuttings and IBA hormonal treatment. In conclusion, hormonal treatment and cutting method are highly recommended for propagation of P.canescens for commercial purpose.